Patterns of tree microhabitats across a gradient of managed to old-growth conditions - Sever, Kristina (Acta silvae et ligni, 2019)
An inventory of tree microhabitats was done in two unmanaged forests (Kobile and Ravna gora forest reserves) and one managed beech forest in SE Slovenia. The purpose of this study was to determine the influence of forest management, natural disturbances, and tree characteristics on microhabitat patterns. Forest structure and microhabitats were recorded in systematically placed plots (500 m2 in size) across each area. In total, we inventoried 849 trees on 54 plots and 1833 tree microhabitats. The results showed that forest management had no significant influence on the abundance of microhabitats per tree, but there were differences regarding microhabitat type between managed and unmanaged sites. There were substantially more microhabitats related to standing dead and live habitat trees in unmanaged forest (e.g. woodpecker cavities, insect galleries and bore holes, branch holes, dead branches and fruiting bodies of fungi), whereas in managed forests there were more tree microhabitats related to management (e.g. exposed heartwood, coarse bark, and epiphytic plants). The results also indicate that disturbance, tree diameter, vitality, and species influence the density, diversity, and occurrence of tree microhabitats.
Keywords: beech forests; biodiversity; bukovi gozdovi; dead wood; drevesni mikrohabitati; forest management; gospodarjenje z gozdovi; gospodarski gozdovi; Kobile; naravne motnje; natural disturbance; negospodarski gozdovi; old-growth; Ravna gora; tree microhabitats; veteran tree